Some Facts that Expand Knowledge about Mykolas Tvarauskas - Raguotis, Bronius (Žurnalistikos tyrimai, 2019)
Mykolas Tvarauskas (1844–1921), the pioneer of the American Lithuanian press, owns the first American Lithuanian publications of various types and genres – English-Lithuanian and Lithuanian English dictionary, poem „I am the first to come to you“, recall „Dear Brothers“ (1875), newspaper „Gazieta lietuviška“ (1879), translation books and other works.
Keywords: M. Tvarauskas; biography; dictionary; American Lithuanians